Prevalence of bovine genital campylobacteriosis and trichomonosis of bulls in northern Nigeria - Mai, Hassan M (BioMed Central, 2013)
BACKGROUND: A survey was conducted to determine the prevalence of campylobacteriosis and trichomonosis, and their concurrence with brucellosis, in cattle in three states of northern Nigeria. METHODS: A total of 602 preputial samples was collected from bulls in 250 herds and tested using culture and identification. Various indigenous and exotic breeds were studied and four major management systems were encountered. Age of the cattle was estimated using dentition, farm records or cornual rings. RESULTS: The estimated true animal-level prevalence of Campylobacter fetus infection was 16.4% (95% CI: 13.0-20.7), of which 18.5% was C. f. fetus and 81.5% was C. f. venerealis. Of the latter, 92% were C. f. venerealis biovar intermedius strains. Animal-level prevalences in Adamawa, Kano and Kaduna states were 31.8%, 11.6% and 8.3% respectively, and were highest in bulls >7 years old (33.4%) and in the Gudali breed (28.8%). Of the 250 herds, 78 (25.5%, 95% CI: 19.4-32.7) had at least one infected bull, and herd prevalence was highest in the pastoral management system (43.5%). After adjustment for confounding using multivariable analysis, the odds of C. fetus infection were highest in Adamawa state (P < 0.01), in the pastoral management system (P < 0.01), and in bulls >7 years old (P = 0.01), and tended to be higher in Bos taurus breeds (P = 0.06). There was a strong positive association between the presence of campylobacteriosis and brucellosis (P < 0.01), both within bulls (OR = 8.3) and within herds (OR = 16.0). Trichomonosis was not detected in any herds. CONCLUSION: Bovine genital campylobacteriosis is prevalent particularly in the pastoral management system in northern Nigeria, with C. f. venerealis biovar intermedius as the major aetiology. There was a strong positive correlation between the occurrence of campylobacteriosis and brucellosis. No evidence of trichomonosis was found in herds in this study.